Efektivitas Visual Art Activities Dan Exercise Snack Terhadap Kualitas Hidup Pada Lansia Di Wilayah Kerja Puskesmas Bandar Khalipah - Sari, Youlanda; Haflah, Nurul; Purba, Dahlia (Universitas Haji Sumatera Utara, 2025)
Elderly people are closely related to various health conditions, especially.physical.health problems. Various theories about the aging process show the same thing. The health status of the elderly that decreases with age.will affect the quality of life of the.elderly. Increasing.age will be accompanied by the emergence.of various diseases, decreased body function, body balance and the risk of falling. The decline in the health status of the elderly is contrary to the desire of the elderly.to remain healthy, independent and able to do activities as usual, such as bathing, dressing, moving independently. The incompatibility of the elderly's condition with their expectations can even cause the elderly to experience depression. Elderly people registered in the Bandar Khalipah Health Center work area experience various health problems. They reported increased uric acid with general complaints of joint pain, hypertension with complaints of frequent dizziness, stroke with complaints of all activities requiring assistance, rheumatism with complaints of swelling in the joints and pain when moving and sleep disorders, from several health problems found that affect their daily activities. There is a demand for elderly fitness training to reduce these health problems. This study examines the effectiveness of visual art activities and exercise snacks on the quality of life of the elderly. Quasy experimental research was conducted to test the hypothesis. A total of 50 elderly people were sampled in this study. The research design used was pre-posttest with control group. The results showed that the quality of life score increased higher in the experimental group than in the control group. The gap in the increased score between the two groups was 6.08 ± 7.55 (p: 0.001). In conclusion, there was a significant difference in scores between the experimental and control groups. Exercise snack can improve the quality of life of the elderly. Health educators are advised to improve the quality of life of the elderly at the Bandar Khalipah Health Center through exercise snack activities.